Violências simbólicas retratadas por fábulas: espaços de diálogo em uma escola estadual de ensino integral - Rosa, Célia Maria (2020)
This work aimed to identify and analyze what Middle School and High School students understood about symbolic violence, with reflection on violence in three planes: in society, school and interpersonal relationships. The hypothesis was that the students realize – when there is dialogue and clarifications – the importance of reflecting on violence in the school environment, and this allows a more welcoming coexistence, preventing conflicts. Otherwise – without reflections on symbolic violence – just a little would be said about the subject. It was held in a full-time public school in the interior of the State of São Paulo and was characterized as an intervention research of an exploratory qualitative character. The students' understanding was analyzed through fables, according to the analysis. It was concluded that: even though they did not have understanding of symbolic violence, students – after exercises provided in elective discipline with open dialogue and explanations of various issues they did not understand – began to see violence, especially symbolic, with another view. In the moral of the fables, discrimination and prejudice of race, ethnicity and beauty were investigated, demonstrating that students understood symbolic violence. On the other hand, they pointed out that breaking with these patterns is something complex and difficult. It is clear that young students expect to be accepted by groups, feeling pain and the need for acceptance, which makes the student reject who she/he is, and become what the group would like her/him to be. Due to the complexity of the theme, investment is indispensable in public policies and also in research and interventions, so that strategies and methodologies capable of acting in contextualized and commited way can be thought of together with the prevention of violence, and then, rescue the socializing function of the school.